Metabolic syndrome in vitiligo patients among a semi-urban Maharashtrian population: A case control study. (November 2017) - Sharma, Y.K.; Bansal, Prakhar; Menon, Shruti; Prakash, Naren
Abstract: Aim: To assess the prevalence of metabolic syndrome and its correlation with the severity and duration of vitiligo. Methods: One hundred vitiligo patients and 100 age-and-sex matched controls were included, whose waist circumference and blood pressure were measured; fasting serum cholesterol, triglycerides and glucose levels quantified; disease severity assessed and metabolic syndrome defined by National Cholesterol Education Program (NCEP) criteria. Results: Metabolic syndrome (24%:12%), hypertriglyceridemia (41%:24%), impaired glucose tolerance (25%:16%) [P < 0.05] and low HDL (P = 0.044) were significantly more prevalent in cases as compared to controls as were the mean values of triglycerides and fasting blood sugar. Increased mean age of vitiligo patients correlated with the presence of metabolic syndrome. Conclusion: Metabolic syndrome had significant presence in but remained unaffected by the severity of vitiligo in our study patients.